Management of severe varus knee osteoarthritis with unconstrained cruciate-retaining total knee arthroplasty using tibial stem and bone grafting: a case report - Balakondaiah, K.; Ramanaidu, P.; Rajkumar, S. (International Journal of Research in Orthopaedics, 2026)
Severe varus knee osteoarthritis associated with medial tibial bone loss presents significant challenges during total knee arthroplasty, particularly in achieving stable alignment while preserving ligament balance. We report the case of a 68-year-old female who presented with severe right knee pain, progressive varus deformity, and inability to ambulate independently. Radiographic evaluation revealed tricompartmental osteoarthritis with collapse of the medial tibial plateau and significant coronal deformity. The patient underwent primary unconstrained cruciate-retaining total knee arthroplasty using a tibial stem extension combined with reconstruction of the medial tibial defect using autologous bone graft and screw fixation. Intraoperative assessment demonstrated intact posterior cruciate and collateral ligaments, allowing the use of a cruciate-retaining implant despite severe deformity. Postoperative radiographs confirmed restoration of mechanical alignment and stable fixation of the components. At one-year follow-up, the patient achieved satisfactory range of motion, pain relief, and functional improvement without evidence of loosening or instability. This case highlights that cruciate-retaining total knee arthroplasty with tibial stem support and bone grafting can be an effective and cost-efficient treatment option for severe varus knees with preserved ligament competence, avoiding the need for constrained implants.